Μέτρηση ενεργού διατομής παραγωγής ζευγών top-antitop quark με τη βοήθεια αδρονικών πιδάκων μεγάλης εγκάρσιας ορμής στο πείραμα CMS - Ανδρεαδάκη, Εμμανουέλα (Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2018)
This note presents a first measurement of the top quark pair production cross section in the fully hadronic decay channel at a center-of-mass energy of √ s = 13 TeV using data corresponding to an integrated luminosity of 3.7 fb−1 taken with the CMS detector. The cross-section is determined from an unbinned maximum likelihood fit to the reconstructed top quark mass. The reconstruction of ttbar candidates is performed after a cut-based event selection using a kinematic fit. A data-driven technique is used to estimate the dominant background from QCD multijet production. The cross-section measurement yields 𝜎𝑖𝑛𝑐𝑙=572±15(𝑠𝑡𝑎𝑡)−48+126(𝑠𝑦𝑠𝑡)+15(𝑙𝑢𝑚𝑖) [𝑝𝑏]. This result is consistent with similar measurements in boosted topologies and within the Standard Model predictions.